Meningkatkan Keterlibatan Kognitif Siswa melalui Project Based Learning dan Pengaruhnya terhadap Sikap Bermedia Sosial - Khanifah, Milatul; Saefudin (Jurnal Pendidikan Agama Islam, 2025)
This study aims to determine the effect of the Project-Based Learning (PjBL) model on knowledge and attitude outcomes regarding the topic of etiquette in using social media. The type of research used is quantitative with a quasi-experimental design, specifically the non-equivalent control group design. The data collection techniques employed were tests and questionnaires. The research instruments consisted of a knowledge test and an attitude questionnaire.This study was conducted at SMK Mulya Husada Purwokerto, with the population being all 11th-grade students and the samples being students from Pharmacy class 1 and Pharmacy class 3. The data analysis technique used was non-parametric tests, namely the Mann-Whitney test.The results of the study showed that the PjBL model can improve both knowledge and attitudes, as indicated by Mann-Whitney test results, with an Asymp. Sig. (2-tailed) value of 0.000, which is less than 0.05. Therefore, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. There is a significant effect of using the Project-Based Learning model in improving learning outcomes in Islamic Religious Education (PAI) subjects for 11th-grade students at SMK Mulya Husada Purwokerto